(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
In spectrum sharing environment, transmit power control strategy has been implemented which enables cognitive secondary user to achieve its required transmission rate and quality, while minimizing interference to the primary users and other concurrent secondary users. In this paper, fuzzy logic is used which an intelligent decision is making tool for transmit power control. Transmit power control strategy is implemented using fuzzy logic system which can tolerate the imprecision and uncertainty of input data like spectrum sensing data and SINR measurements in this case. For the performance enhancement, compressive sensing is applied which lowers the number of samples in order to obtain the modified signal. Here the probability of missed detection and probability of false alarm is calculated which gives the information about active primary users.